Empirical Study on Electronic Learning System: Benefits, Challenges and Prospects - Najeem Olawale Adelakun; Samuel Adeniyi Omolola; Azeez Olamilekan Mosaku; Matthew Saint Adebola (International Journal of Science Education and Cultural Studies, 2022)
The swift growth of digital technology has led to the adoption of emerging technologies in all human endeavours. Over the years, the rate of smartphone users has increased rapidly which makes so many developed nations adopt online learning as a means of taking education to everyone irrespective of their geographical location. Similarly, the COVID-19 outbreak makes so many developing countries adopt the electronic learning system as a viable approach to teaching and learning. Consequently, the e-learning system is useful for the creation of informative online sessions, supplementary lessons for students, webinars, e-mentoring and online conferences. This paper uses an empirical approach to evaluate the benefits and challenges associated with the e-learning system, and a survey was conducted among students in a higher institution in Nigeria to know the likely challenges faced by students with the e-learning system and also at different online researchers forum across the globe. A total of four hundred and ninety-five (495) responses were gathered and the data was analysed using descriptive statistics. The result shows that 33.94% of students complained about weak internet connectivity from the questionnaire administered which is also a major problem in most developing nations, while only 7.27% of respondents complained about limited feedback, it is recommended that there should be a provision of standard IT infrastructure, strong internet connectivity, and user-friendly e-learning platform, its implementation will improve performance and lead to greater productivity.